Clinical and radiological outcome after anterior cruciate ligament reconstruction using the T-lock Osteotrans resorbable tendon anchor: early experience and midterm follow-up - Bangert, Yannic; Jaber, Ayham; Wünnemann, Felix; Berrsche, Gregor; Streich, Nikolaus; Rehnitz, Christoph; Ott, H.; Barié, Alexander (BMC musculoskeletal disorders, 2020)
Reconstruction of the Anterior cruciate ligament (ACL) using tendon grafting is an established method for restoring knee function and stability. Multiple methods are established for graft fixation. Several involve anchoring the autograft distant to the joint with hardware that remains implanted. This study reports the first early to midterm results in patients who received ACL reconstruction (ACLR) using the T-Lock Osteotrans femoral near joint fixation method with a tibial fixation using the BioactIF Osteotrans interference screw.
Gesehen am 18.10.2021